Short term outcomes of laparoscopic surgery after treatment of colorectal cancer - Salam, M. Abdus; Haque, M. Ekramul; Mallick, Mithun Kumar; Siddiq, M. Erfan; Rahman, Mizanur; Masum, Mahmudul Hasan; Islam, Muhammed Najibul; Rahman, Mohammed Ashrafur (International Surgery Journal, 2024)
Background: Colorectal cancer is a significant health concern globally and in Bangladesh. Laparoscopic surgery is increasingly used for its treatment due to its minimally invasive nature, but comprehensive data on its short-term outcomes and complications in the Bangladeshi population is limited. Methods: This prospective observational study was conducted from September 2018 to October 2019 at the Department of Surgical Oncology, National Institute for Cancer Research and Hospital, Dhaka. Thirty-nine patients diagnosed with colorectal cancer and undergoing laparoscopic surgery were included. Data on demographics, clinical presentations, colonoscopy findings, operative details, and postoperative outcomes were collected and analyzed using SPSS for Windows, version 22.0. Results: The study population consisted of 58.97% males and 41.03% females. The most common chief complaints were per-rectal bleeding (48.72%) and abdominal pain (17.95%). Colonoscopy findings revealed ulcer proliferative lesions in 64.10% of patients. The mean operation time was 159.36 minutes, and the mean approximate blood loss was 124.5 ml. The mean postoperative hospital stay was 4.56 days. Minor postoperative complications included urinary tract infections (30.77%) and perineum infections (15.38%), while major complications included surgery conversion (12.82%) and postoperative mortality (2.56%). Conclusions: Laparoscopic surgery for colorectal cancer offers significant benefits, such as reduced operative time, lower blood loss, and shorter hospital stays. However, the incidence of postoperative complications remains a concern, highlighting the need for improved surgical techniques and postoperative care. Addressing these challenges is crucial for optimizing patient outcomes and enhancing the adoption of laparoscopic surgery in Bangladesh.